Equilibrium swelling of polystyrene by alkanes and carboxylic acids : a simple quantitative correlation model - Bernardo, Gabriel (2010)
In this study, we show that the equilibrium saturation swelling of polystyrene by linear alkanes and linear carboxylic acids, as reported earlier (Bernardo and Vesely, Eur Polym J 2007, 43, 4983, Bernardo and Vesely, J Appl Polym Sci 2008, 110, 2393) can be correlated quantitatively using a model where only the alkylchain lengths and the saturated vapor pressures of the organic liquids are considered. According to this model, at very low vapor pressures, the number of polystyrene monomer units per solvent molecule is directly proportional to the alkyl chain length of the solvent molecule under consideration. At higher vapor pressures, the number of polystyrene monomer units per solvent molecule tends to become independent of its alkyl chain length.